Movement symmetry and asymmetry of goal shots in female football at European championships and at World Cup - Wlodzimierz, S.; Josef, B.; Andrzej, S. (African Journal for Physical, Health Education, Recreation and Dance, 2011)
This study examined the phenomenon of symmetrical skills in goal shot technique in female football players, of nine video recorded matches. The recording was taken during the 2nd Under 19 female football World Cup in 2004 and the 6th European female Championships of female seniors in 2005. The study comprised field zones, goal sectors and topography of scored goals. It was carried out with the use of match observation sheets. Results of observations pointed to clear domination of shots made with the right leg - 73.8% in female juniors and a slightly smaller domination - 68.6% in female seniors. Full movements symmetry was found in young Brazilian female football players, and the highest level of symmetrical skills in female seniors was displayed by the team from England. The study noted the existence of a rare skill of dominating left leg in female juniors of Australia and Canada, and in female seniors from France. The best teams had asymmetrical skills with right leg dominance. Female junior world champions, such as for example the German national team, had the highest number of athletes making bilateral kicks (right and left). As regards the majority of female seniors, more versatile skills (60.0%) were reported. A lower number of "two-footedness" football players was only found in the Danish national team. It was also established that female juniors tended to make more kicks from the left field zone, while female seniors were from the right. Kicks at goal sectors (left and right half) were made almost symmetrically, and in the majority of cases the lower lateral sectors were hit. Over 28.0% of female seniors and female juniors were found to be characterised by a high practical efficiency index. This index could result from less efficient tactical actions in defence, as well as inferior preparation level of female goal keepers. The results indicate that top world teams have female players with symmetrical preparation, i.e. two-footedness skills. The results of these observations provided a basis for formulation of methodological recommendations for training female football players.